Cytogenetically normal acute myeloid leukaemia at a single centre in South Africa - Jenkins, Nicholas (Department of Clinical Laboratory Sciences, 2022)
Introduction The heterogeneous molecular landscape of cytogenetically normal acute myeloid leukaemia (CN-AML) renders it an ongoing therapeutic challenge worldwide. The latest European LeukaemiaNet (ELN) 2017 guidelines attempt to address this by guiding post-remission therapy according to six prognostically informative mutations. However, its applicability in a South African setting remains elusive due to limited local data. This retrospective study aimed to describe a South African CN-AML cohort according to clinicopathological, molecular and treatment outcomes and consequently investigate the local applicability of a triple mutation testing approach for nucleophosmin (NPM1), fms-like tyrosine kinase internal tandem duplication (FLT3-ITD) and CCAAT/enhancer binding protein alpha (CEBPα) mutations in accordance with the ELN 2017 guidelines. Methods A review of cytogenetic results for all adult de novo AML cases diagnosed at Groote Schuur Hospital between 2005 and 2018 was performed. CN-AML cases were further characterized via molecular testing and review of clinical and laboratory data. Results In total, 218 patients with AML were identified of which fifty-six (33%) were cytogenetically normal. NPM1, FLT3-ITD and CEBPα mutations were found in 39%, 34% and 9% of CN-AML cases respectively, and allowed for definitive prognostication of 50% of cases. The 2-year overall survival rate for the entire CN-AML cohort was 16%. Conclusion Local rates of CN-AML and associated NPM1 and FLT3-ITD mutations were comparable to European cohorts. In contrast, local survival outcomes were notably inferior. Triple testing proved a resource effective prognostication approach for CN-AML. High throughput sequencing for adverse risk mutations should be considered for CN-AML patients inconclusively stratified via triple testing.